Typological, Synchronic and Diachronic Analogies from the Medieval Period in Săbăoani locality, Neamț county, Romania - Robert Simalcsik (Anastasis: Research in Medieval Culture and Art)
The underlying material for the present study is represented by the human skeletons from two necropolises located in the area of Săbăoani commune (Neamţ county) and which are significantly important for the history of this community. Another feature we favored in the present study is the anthropological type that gathers all individuals of a population which represents a certain association of characters. Within Săbăoani community, chronologically (diachronically) speaking we can notice the perennization of the Mediteranoid medieval anthropological fund. Dinaroid elements have registered a continuous increase along with the Nordoid elements and consequently reached a top position among nowadays population, we also notice the appearance of Mongoloid elements in the medieval period. Several generations should succeed in the case of some dominant elements of the typological fund. The blend of typological features and their percentages have broadly modified along with the individual/ population migration from one place to another.